Note on the Intellectual Work of William Stainton Moses - Alvarado, Carlos S. (Journal of Scientific Exploration, 2018)
Most discussions about William Stainton Moses have focused on his mediumship. This note is a reminder that, in addition to mediumship, such as the spirit communication recorded in Spirit Teachings (1883), Moses contributed in various other ways to the study of psychic phenomena. This included studies of direct writing, materializations and spirit photography. Furthermore, Moses wrote about apparitions of the living and out-of-body experiences, veridical mediumistic communications, and criticized the writings of others, among them, physiologist William B. Carpenter. A consideration of this, and other neglected aspects of Moses’ work enlarges our view of his contributions to Nineteenth-Century British Spiritualism and psychical research.